The Role of Teachers in Developing Contextual Mathematics Learning Based on the World of Work in Grade XII of Vocational Schools - Dwi Arifa; Zaenuri Zaenuri (Jurnal Penelitian Pendidikan, 2026)
The low motivation of students to learn where the perception that mathematics is less relevant in the world of work is a challenge in learning mathematics in Vocational High School (SMK) grade XII. In fact, metamatics has an important role in the world of work and is a supporter of vocational competence, especially the work readiness of vocational school graduates. An approach that is able to bridge these gaps is contextual mathematics learning based on the world of work. The purpose of this article is to examine the role of mathematics teachers in contextual mathematics learning based on the world of work in grade XII of vocational schools. The use of the literature study method for national and international journal articles for the 2021-2025 period is a support in the preparation of articles. The results of the study show that mathematics teachers have a strategic role as designers of learning contexts, facilitators of authentic learning experiences, and motivation to students. Contextual mathematics learning based on the world of work is able to increase students' involvement, understanding of concepts, and positive attitudes towards mathematics lessons. This article recommends strengthening the competence of vocational mathematics teachers in designing contextual learning so that mathematics becomes more meaningful and relevant for grade XII students at vocational schools.